FRI0443 IMPACT OF APREMILAST ON PSAID CORE COMPONENTS IN PATIENTS WITH A LIMITED NUMBER OF ACTIVE JOINTS: RESULTS FROM THE REAL-WORLD, PROSPECTIVE, MULTICENTRE REWARD STUDY. (June 2019) - Jansen, Tim; Kroot, Eric-Jan; Vliet, Arie van; Pander, Jan; Vis, Marijn
Abstract : Background: Recent data suggest that patients with moderately active psoriatic arthritis (PsA) and a limited number of active joints have a high likelihood of achieving treatment goals with apremilast treatment. 1, 2 Real-world evidence on the effect of apremilast on patients' perception of the impact of their disease is limited. Objectives: To describe the effects of apremilast on the impact of disease in the real world as measured by the Psoriatic Arthritis Impact of Disease (PsAID) questionnaire in PsA patients with SJC ≤4 at baseline. Methods: The prospective, multicentre, observational REWARD study (The Netherlands) is investigating apremilast treatment in real-world patients with PsA. Descriptive statistics were assessed for disease measures, including swollen joint count (SJC; 0-66) and tender joint count (TJC; 0-68), PsAID (0-10) and patient's perception of pain based on the visual analog scale (VAS; 0-100 mm) among patients with limited number of swollen joints (SJC ≤4) at baseline. We report the effects of apremilast on these disease measures at treatment initiation and at the first 6 months of treatment with a data cutoff of December 2018. Results: A total of 48 patients from 9 clinics who were receiving apremilast were included in this interim analysis. Among these patients, 31 (65%) had SJC ≤4 and 17 (35%) had SJC >4 at baseline. Of patients with SJC ≤4 at baseline, 18 and 8 had at least 3 and 6 months of follow-up, respectively, at the time of data cutoff. Results are reported for patients with available data at each time point. Baseline characteristics for patients with SJC ≤4 included a mean age of 54 years, mean BMI of 29.1 and mean years since PsA diagnosis of 7.0 years; 58% of patients were female, 90% had prior cDMARD use and 29% had prior biologic use. For patients with SJC ≤4, disease measures were reported as follows: The mean SJC at baseline, 3 and 6 months were 1.1, 0.6 and 0.1 and the mean TJC at baseline, 3 and 6 months were 4.5, 3.6 and 1.5. The mean PsAID scores at baseline, 3 and 6 months were 4.2, 3.4 and 2.6. Individual PsAID domain scores by time points are shown (Figure). Patients with a limited number of swollen joints showed gradual improvements in all domains of the PsAID. Mean Pain VAS scores at baseline, 2 weeks, 6 weeks, 3 months and 6 months were 47, 48, 39, 29 and 26 in these patients. Conclusion: Results from the real-world, prospective, multicenter, observational REWARD study suggest that PsA patients with a limited number of active swollen joints may benefit from apremilast treatment. Apremilast was associated with improvements in the perceived impact of disease, as observed by reductions in the PsAID and its core components. References: [1] McInnes I, et al. Ann Rheum Dis. 2018;77(Suppl 2). Abstract 0927. 2. Coates LC, et al. Arthritis Rheumatol.2018;70(Suppl 10). Abstract 1607. Disclosure of Interests: Tim Jansen Grant/research support from: Olatec, Consultant for: Abbvie, Celgene, Menarini, Novartis, Speakers bureau: Grünenthal, Eric-Jan Kroot: None declared, Arie van Vliet Employee of: Celgene Corporation, Jan Pander Employee of: Celgene Corporation, Marijn Vis Grant/research support from: Novartis